STUDY OF THE PREVALENCE OF INTESTINAL PARASITIC INFECTIONS AMONG CHILDREN IN SHATRAH DISTRICT / THI-QAR PROVINCE - SOUTH OF IRAQ - AL-Gorani, Amal F. (PT. Antis International Publisher, 2024)
The current study aimed to determine the prevalence of intestinal parasites among children from newborns to ten years of age in different areas affiliated with the Shatra district in Dhi Qar Governorate in southern Iraq, as these areas suffer from poor health and living services in addition to a lack of awareness and interest in personal and health hygiene. The study was designed by taking 100 A random sample from different areas. The results were 25% of healthy children, while 75% were infected. The widespread infections were with the parasites Giardia lamblia and Entamoeba histolytica. The results confirmed that most of the infected children were between two and four years of age, in addition to the fact that the most common infections were the combined infections of the Entamoeba parasite and Giardia for the same infected people, with a very high rate of up to 56%, while the infection of children with the Entamoeba parasite alone was 18.7% and Giardia alone was 25.3% in addition. The percentage of females is 65% while the percentage of males is 35% in parasitic infections and The infection rate in the countryside was higher than the infection rate in cities, as the infection rate in the countryside was (55%) and in the cities (45%).